(untitled) (Journal of Nuclear Technology in Applied Science, 2022)
A pot experiment was carried out in greenhouse to study the effect of Lead (pb) applied as a toxic metal with and without Molybdenum (MO) on growth, dry matter yield of chickpea plants and N fixation using 15N dilution technique. The experiment was laid out in randomized complete block design in three replicates of each treatment. Before sowing, the legume chickpea seeds inoculated with Rhizobium Leguminesarum.. Lead was applied as lead sulfate at rates of 0, 50 and 100 mg Pb kg-1 soil, while, Molybdenum was applied as Molybdenum sulfate at levels of 0, 1, 2 and 3 mg MO kg-1 soil. Results demonstrated that, in general trend, the highest weights of seeds and shoots were 15.36 g pot-1 and 19.68 g pot-1 observed in the pots received rate of (Pb 0 + Mo 3) ratio, respectively. For N-uptake by seeds and shoots, the highest values were 763.87 mg pot-1 and 324.34 mg pot-1 achieved in the pots received rate of (Pb 0 + Mo3) ratio. While for pb-uptake by seeds and shoots, the highest values were 8.0 mg pot-1 and 43.0 mg pot-1 achieved with the rate of (Pb 100 + Mo 0) ratio. Using 15N dilution technique, in seeds, the highest value of (Ndff%) was (11.85%), achieved with rate of (pb 50 +Mo3) ratio and dose of (pb100 + M1) ratio while, the highest value of (Ndfa%) was (40.21%), achieved with rate of (pb100 +M1) ratio and followed by (39.81%) with dose of (pb100 + Mo2) ratio, respectively.